Level of Satisfaction in Post-Operative Patients in Surgical Wards of Bahawal Victoria Hospital (BVH), Bahawalpur (Medical Forum Monthly, 2024)
Objective: To determine the factors that affect patient satisfaction and to explore the aspects of care provided by the doctors in surgical wards of Bahawal Victoria Hospital in order to improve the overall satisfaction level of the patients.Study Design: Descriptive / cross sectional studyPlace and Duration of Study: This study was conducted at Bahawal Victoria Hospital, Bahawalpur was from March 2016 to June 2016.Materials and Methods: A sample of 100 patients by convenient sampling technique was taken from surgical wards (S1, S2, S3, and S4) of Bahawal Victoria Hospital, Bahawalpur. Of 100 participants, 57 were males and 43 were females. Data was analyzed by using software SPSS 15.0 Demographic table frequencies and percentages were constructed.Results: A total of 100 subjects were interviewed. Among them, 24% were highly satisfied, 75% of the subjects were moderately satisfied, and only 1% was not satisfied. A total of 93% of the patients gave positive response about ease of admission into the ward. In domain of Physical Examination, overall 86% people were fully satisfied and 14% were not satisfied.Conclusion: Most of the patients were satisfied regarding ease of admission in the ward, behavior of doctors & nursing staff and their availability during any distress. Domains of sanitary conditions and food availability as well as its quality & hygiene need further attention.